Narcissistic Personality Disorder In The Novel Best Day Ever By Kaira Rouda - Warham, Warham; Moelier , Dahlia D.; Abeng, Andi Tenri (Fakultas Sastra, Universitas Bosowa, 2024)
This study aimed to identify the causes and types of narcissistic personality disorder in the main character of Kaira Rouda's novel,